Peranan Wali Murid dan Guru pada Kurikulum Merdeka - Mahfudh (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The purpose of this study is to describe how the role of a parent and teacher in the era of Independent Learning curriculum today. The research method used is literature research or literature study by reviewing various literature relevant to the theme of research and also the interview process between parents and teachers and this article uses a photo attachment during the interview procession. The results of this study indicate that the role of parents with teachers is very important in the implementation of the independent learning curriculum. But again in implementing a curriculum that requires a habituation so that the program is carried out properly, because there are still some people still do not really understand what the meaning of independent curriculum whether it is from the side of teachers and parents. From these conditions, it can be possible to socialize the implementation of the independent curriculum in advance to related parties, especially teachers and parents, so that the independent curriculum runs well, students are happy and can accept what it means to learn, and feel happy and comfortable with learning itself